Problem Based Learning: Peningkatan Hasil Belajar Fikih Materi Qurban dan Aqiqah pada Siswa di MTs Negeri 10 Sleman - Andaryati, Erni (Jurnal Pendidikan Madrasah, 2023)
This study aims to identify the effectiveness of the Problem Based Learning (PBL) method on student learning outcomes in Fikih lessons. This study used classroom action research methods. The subject of the study was a student of MTs Negeri 10 Sleman. Research is carried out in two cycles including planning, implementation, observation, and reflection activities. The results showed that the learning outcomes of students experienced a significant increase, from 47% increased to 79% in cycle 1 and 97% in cycle 2. The problem-based learning method can be applied to Jurisprudence subjects at the madrasah level. Improvement in learning outcomes can be seen from the form of change, namely: habits, skills, observation, associative thinking and memory, rational and critical thinking, attitudes, appreciation, and effective behaviour. At the MTs level, Fikih subjects are subjects that are directed to prepare students so that students can know, understand, and practice Islamic sharia which is the basis of their view of life in society.